GERAKAN PERPAG (PERSATUAN RAKYAT PENYELAMAT KARST GOMBONG) DALAM MELAKUKAN PENOLAKAN TERHADAP PEMBANGUNAN PT. SEMEN GOMBONG) - Ichza Ardiansya (Jurnal Analisa Sosiologi, 2024)
This study aims to analyze the strategies, success factors, and challenges faced by the PERPAG (People's Association of Karst Gombong Rescuers) movement in rejecting the development of PT. Semen Gombong in Kebumen Regency. Social movements become agents to fight for democratic rights, justice, and forgiveness of the people from dissatisfaction with unfair treatment. PERPAG is one of the social movements in Indonesia to date that has been able to thwart the cement company's efforts to exploit limestone. The method used is qualitative research using a case study approach. The study's results show the background of the PERPAG movement with the plan of PT. Semen Gombong to explore limestone in the South Gombong Karst Landscape Area which is considered to damage the ecosystem. Then the PERPAG movement does not only use one strategy such as coercion to the relevant government, this movement elaborates several strategies in its objectives. The emergence of various inhibiting factors (internal and external) cannot be separated from the journey of the movement. Still, PERPAG's consistency has resulted in success with the unsuccessful efforts of PT. Semen Gombong to explore the limestone.